Use of digital educational resources by educators in the early grades of elementary school - Dos Santos, Gislene Munhoz [UNESP]; Casarin, Helen de Castro Silva [UNESP]; de Almeida, Cátia Cândida [UNESP]; Lucas, Margarida (FapUNIFESP (SciELO), 2022)
The use of digital educational resources is a contemporary requirement. Basic education teachers need to be prepared for the proper and emancipatory use of these resources. This research verifies how teachers from the municipal education network in the countryside of São Paulo state in Brazil, have used digital resources in teaching-learning activities, comparing them with variables such as sex, age and time of acting using the DigCompEdu Check In. The instrument was applied to all teachers in the municipal education network. 1348 questionnaires were returned. It was found out that, in general, teachers have used the Internet to search for information and consider suitability to their students as a selection criterion. As for the use of digital resources, they are restricted to simpler activities, such as preparing presentations. It was also found out that most participants are concerned with protecting sensitive data and content, but they still should improve their skills in relation to this issue. It is concluded that there is a need to complement the training of educators in the location where the research was performed.
Uso de recursos educativos digitais por educadores das séries iniciais do ensino fundamental
Keywords: Digital competence; Digital educational resources; User studies